Women's Bargaining Power and Children's Schooling Outcomes: Evidence From Ghana. Issue 3 (2nd July 2020) - Afoakwah, Clifford; Deng, Xin; Onur, Ilke
ABSTRACT: This study uses data from the Ghana Living Standards Survey to examine the link between women's bargaining power and children's schooling outcomes. It employs a principal component analysis to generate an index measuring women's bargaining power based on a couples' education gap and age gap when their child reaches age 6. It then uses women's age at first marriage as an instrument to identify women's bargaining power. The results show that women's bargaining power holds no significant association with late school enrollment. However, it has a negative and significant association with the probability and intensity of grade repetition (the number of times the same grade is repeated), especially for firstborn children. Girls tend to benefit more from the mother's bargaining power compared to boys. The study further shows that women's bargaining power is linked with school enrollment and attainment, which confirms previous findings in the literature. Highlights Slow school progression caused by late enrollment and grade repetition is a problem worldwide, especially in developing countries. This study examines the impact of women's intrahousehold bargaining power on children's schooling outcomes in Ghana. Increased women's bargaining power has no effect on the timing of school enrollment but reduces the chances of grade repetition and how many times the same grade is repeated. Girls benefit more from their mothers' bargaining power compared to boys. Women's bargaining power has a larger impact on the education of firstborn children than on subsequent children. Policies aimed at empowering women will improve children's schooling outcomes.